(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate several factors related to the outcome of shoulder rehabilitation after arthroscopic rotator cuff tendon repair surgery at Military Hospital 175. Research methodology: 108 patients diagnosed with rotator cuff tendon tears and treated with arthroscopic surgery at Military Hospital 175 between April 2025 and March 2026, followed by continued rehabilitation at rehabilitation centers or self-training according to the protocol. Results were assessed using the UCLA score, VAS pain score, shoulder range of motion, and rotator cuff strength 12 weeks post-surgery. Results: After 12 weeks of rehabilitation, the rate of improvement in shoulder function after arthroscopic rotator cuff tendon repair surgery reached 87%. The group undergoing rehabilitation at healthcare facilities had a higher rate of functional improvement than the group self-rehabilitating at home (94.5% vs. 79.2%; OR = 4.54; p < 0.05). Statistically significant factors associated with rehabilitation outcomes included gender (p = 0.006), residential area (p = 0.031), and adherence to the rehabilitation program (p = 0.014). Conclusion: After arthroscopic rotator cuff tendon surgery, the combination of early rehabilitation and adherence to the rehabilitation program is crucial in optimizing patient recovery outcomes.